Efektivitas Pupuk Kotoran Sapi dan Trichoderma harzianum pada Tanaman Bawang Merah (Allium ascalonicum L.) - Erianti Erianti; Rusmana Rusmana; Imas Rohmawati; Putra Utama (Jurnal Ilmiah Membangun Desa dan Pertanian, 2025)
Shallots are one of the horticultural crops with the best chances of being consumed in large quantities in the community. Low shallot output, however, leads to uncertain shallot pricing—soil degradation results from farmers’ widespread use of inorganic fertilizers. Therefore, organic fertilizer that is safe for the environment must be used. This research will investigate the effects of Trichoderma harzianum and cow dung fertilizer on the growth and yield of shallot plants (Allium ascalonicum L.). The research was conducted in the Banten Agricultural Instrument Standard Assessment Center’s Screenhouse from May to July 2024. The study used two variables: the Factorial Randomized Complete Block Design (RCBD). Three repetitions of each therapy resulted in 48 treatment combinations. Cow manure dosages are the first factor: 0 g/polybag, 31.4 g/polybag, 62.8 g/polybag, and 94.2 g/polybag. The second element is Trichoderma harzianum dosage, which may be 0, 4, 7, or 10 g/plant. If a difference is found after a variance analysis at the 5% level, a DMRT is performed at the 5% level. The following attributes were measured: fresh weight, dry weight, bulb weight, number of leaves, bulbs, and bulb diameter. Findings showed that the 94.2 g/polybag dose of cow dung fertilizer affected the quantity of leaves, fresh weight, dry weight, and bulb weight. On leaf number 4 WAP, Trichoderma harzianum (7 g/plant) and cow manure fertilizer (62.8 g/polybag) interacted.